In Vitro Microleakage of Mineral Trioxide Aggregate, Calcium-Enriched Mixture Cement and Biodentine Intra-Orifice Barriers - Ramezanali, Fatemeh; Aryanezhad, Sasan; Mohammadian, Fatemeh; Dibaji, Fatemeh; Kharazifard, Mohammad Javad (Iranian Endodontic Journal, 2017)
Introduction: This in vitro study compared the coronal microleakage of mineral trioxide aggregate (MTA), calcium-enriched mixture (CEM) cement and Biodentine as intra-orifice barriers. Methods and Materials: The study was conducted on 76 extracted single-canal human teeth. Their root canals were prepared using ProTaper rotary files and filled with gutta percha and AH-26 sealer using lateral condensation technique. Coronal 3 mm of the gutta percha was removed from the root canals and replaced randomly with MTA, CEM cement or Biodentine in the three experimental groups (n=22). A positive and a negative control group were also included (n=5). The entire root surfaces of all teeth were covered with two layers of nail varnish in such a way that only the access openings were not coated. In the negative control group, the access opening was also coated with nail varnish. All teeth were immersed in India ink and after clearing, the samples were evaluated under a stereomicroscope under ×10 magnification to assess the degree of dye penetration. The data were analyzed using the Kruskal-Wallis test. The level of significance was set at 0.05. Results: The negative control group showed no leakage while the positive control group showed significantly higher microleakage than the test groups (P>0.05). CEM cement had the lowest (0.175±0.068 mm) and MTA showed the highest dye penetration (0.238±0.159 mm) among the experimental groups; although these differences were not statistically significant (P=0.313). Conclusion: CEM cement exhibited the least microleakage as an intra-orifice barrier in endodontically treated teeth. Keywords: Biodentine; Calcium-Enriched Mixture; Intra-Orifice Barrier; Microleakage; Mineral Trioxide Aggregate